Belajar membuat buku digital pada sistem Android: Satria Novari (Universitas Mahakarya Asia, 2021)
The purpose of this study is to create an easy and practical learning media that can be used in the learning and teaching process among teachers and as learning. As for the background of this writing because of the amount of time wasted when looking for textbooks at home or forgetting to put the book and not to mention having to use a lot of places to store the textbooks, textbooks also cannot be read anywhere and anytime because readers may find it difficult when carrying a lot of books to read By making a digital book at SMK Negeri 3 Ogan Komering Ulu Selatan, this method uses data collection by taking data at SMK, including interviews with the student body and students. The research was conducted in March 2021. The software used to create this application is using Android Studio, CorelDRAW X4 and Reduce PDF Size. This application can display textbooks where if you click on the name of the book a softcopy will appear. and there are several books that can be used as guidelines for student learning. In this media, the writer completes it with a backsound so that the reader is more relaxed while reading.